Increase of serum pancreatic enzymes during hospitalization for acute heart failure - Marlene A.T. Vijver; Olivier C. Dams; Jozine M. terMaaten; Iris E. Beldhuis; Kevin Damman; Adriaan A. Voors; Robert C. Verdonk; Dirk J. vanVeldhuisen (ESC Heart Failure)
Aims Acute heart failure (AHF) is associated with end‐organ dysfunction. The effect of AHF on the pancreas has not been studied. We aim to evaluate serum markers of pancreatic damage during hospitalization for AHF. Methods and results In data from the Pragmatic Urinary Sodium‐based treatment algoritHm in Acute Heart Failure (PUSH‐AHF) study, amylase and lipase values were extracted from available serum samples at baseline, and at 24 and 72 h after hospitalization. The differences between pancreatic enzymes between timepoints were evaluated using the Friedman test. Associations with N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) were tested using linear regression analysis. The study population consisted of 274 patients. Mean age was 73 ± 11 years, and 117 (43%) were women. Mean left ventricular ejection fraction (LVEF) was 38 ± 14%; 53 (19%) patients had HF with a preserved LVEF (≥50%). At baseline, median amylase and lipase were within normal range (47 [33–63] U/L and 30 [21–44] U/L, respectively). Both enzymes significantly increased in the first 72 h (P‐value for trend <0.001); mean change was 9 ± 22 U/L for amylase, and 10 ± 22 U/L for lipase. Moreover, NT‐proBNP at baseline showed a positive correlation with mean change in pancreatic enzymes in 72 h (P = 0.02 for amylase and P = 0.006 for lipase). Conclusion Patients admitted for AHF exhibited a significant increase in serum values of pancreatic enzymes in the first 72 h, suggesting that an episode of AHF affects the pancreatic tissue. This rise in pancreatic enzymes was associated with HF severity, as reflected by NT‐proBNP.